Visits to Sacred Places from Buddhist Perspective - Paudel, Yog Raj (AWADHARANA, 2024)
This writing introduces the rationale of undertaking a pilgrimage from the Western perspective particularly focusing on Mircea Eliade’s “Centre of the World” view point. The main objective of the research was to explore why foreign tourists visit Buddhist sacred place like monastery and perception of monks and nuns to foreign visitors. It has included nine monasteries of Pokhara valley. First, this paper pays glimpse on general understanding of ‘pilgrimage’ from the Buddhist perspective. This is qualitative research. The secondary data were collected from books, journals, etc. and the primary data were through field visits, asking participants’ responses to prepared questionnaires as well as contextual questions. It has used inductive reasoning on interviews, responses to questionnaires and informal discourses of the respondents. The analysis and conclusion are mostly based on primary data. The findings indicate that foreign visitors’ entertainment purpose, will to meditation as well as faith and devotion to the Buddha and Buddhism motivate them to visit monasteries. The sightseeing purpose is kindled by respect to Buddhism and curiosity to know environment of Buddhist religious practices in Nepal in general and Pokhara in particular. The attitude and perception of monastery monks and nuns in receiving visitors and tourism was found to be positive and, in practice, the monks and nuns were mostly welcoming and supportive to foreign visitors.